Research Progress on Multimodal Analgesia for Preventing Postoperative Pain Following Extraction of Impacted Mandibular Third Molars - Guo, Chenyu; Zhang, Bori (International Journal of Public Health and Medical Research, 2025)
Pain, as a common complication after the extraction of impacted mandibular third molars, significantly affects patients' physiological functions, social activities, and psychological well-being. Given that traditional analgesic methods are often accompanied by numerous side effects, multimodal analgesia strategies have emerged and gained widespread advocacy. This strategy involves precise pain assessment and the combined use of multiple analgesic drugs with different mechanisms of action, along with non-pharmacological treatments, aiming to achieve optimal pain relief while minimizing adverse reactions. This article reviews the pain assessment methods, non-pharmacological treatments, and pharmacological regimens within the multimodal analgesia strategy, with the goal of providing scientific evidence and practical guidance for pain management in patients undergoing impacted mandibular third molar extraction.